(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The forced transition to distance education led to the search for non-traditional forms of conducting physical education classes. One of the effective ways to solve the problem of increasing the motor activity of student youth during distance learning was the development and implementation of new fitness technologies based on the conscious attitude of students to their own health and physical self-improvement. The article analyzes the content of students’ physical self-improvement technologies that were successfully used during distance learning during the period of the Covid-19 quarantine restrictions. The authors have developed a new technology "The Way of Independent Physical Improvement", which is based on the advantages of the fitness program "The Way to a Healthy Life". The new technology is supplemented by two content modules and has a significantly larger number of physical exercises that can be performed both indoors and outdoors, individually or as part of a group. 476 students (229 women, 247 men) from four higher educational institutions took part in the study. The purpose of the article is to study the effectiveness of the fitness technology "Path of independent physical improvement" on the development of motor skills and functional health indicators of students during distance learning. Research methods included: analysis of scientific and methodical sources, survey, pedagogical experiment, pedagogical observation, method of expert evaluation, methods of research of indicators of functional and physical condition of students, comparative analysis, methods of mathematical statistics. The results of the experiment showed that the students had positive changes in the functional indicators of the development of the respiratory system, the physical performance of the cardiovascular system, and in the improvement of indicators of recovery processes after physical exertion. In the development of students’ physical abilities, reliably significant positive changes occurred in indicators of strength development, speed-power abilities, and general coordination of movements. Other indicators of physical development remained at the previous level. Conclusions. The technology "Path of independent physical improvement" has a positive effect on the development of motor skills and functional health indicators of students and can be implemented during distance learning.